Ti4O7/g-C3N4 Visible Light Photocatalytic Performance on Hypophosphite Oxidation: Effect of Annealing Temperature - Guan, Wei; Sun, Gaoge; Yin, Lei; Zhang, Zhenghua; Tian, Shichao (Frontiers in Chemistry, 2018)
The oxidation of hypophosphite to phosphate is the key to recover the phosphorus resource from the hypophosphite wastewater. In the present work, Ti4O7/g-C3N4 composites were synthesized at two different temperatures (100 and 160 °C) and their performance on photocatalytic oxidation of hypophosphite under visible light irradiation and the corresponding mechanism were evaluated. A hydrolysis method using g-C3N4 and Ti4O7 was applied to synthesize the Ti4O7/g-C3N4 composites with their hybrid structure and morphology confirmed by XRD, SEM and XPS. The annealing temperature significantly affected the photocatalytic performance of Ti4O7/g-C3N4 that the 160-Ti4O7/g-C3N4 composite (fabricated at 160 °C) showed the highest oxidation efficiency of hypophosphite of 81% and the highest photocatalytic oxidation rate of 0.467 h-1 comparing with the 100-Ti4O7/g-C3N4 composite (fabricated at 100 °C) and pure g-C3N4. The enhanced photocatalytic performance of 160-Ti4O7/g-C3N4 could be ascribed to the effective charge separation and enhanced photoabsorption efficiency. Additionally, electron spin resonance (ESR) results showed that hydroxyl radicals and superoxide anion radicals were mainly responsible to the oxidation of hypophosphite with superoxide anion radicals accounting for a more significant contribution. Moreover, Ti4O7/g-C3N4 photocatalysts showed the remarkable stability in the repetitive experiments.